Basics of qualitative research : techniques and procedures for developing grounded theory. - Corbin, Juliet M., 1942-; Strauss, Anselm L., 1916-1996 (Los Angeles : SAGE, 2008)
The Third Edition of the bestselling Basics of Qualitative Research:Techniques and Procedures for Developing Grounded Theory continues to offer immensely practical advice and technical expertise to aid researchers in making sense of their collected data. Authors Juliet Corbin and the late Anselm Strauss (co-creator of Grounded Theory) present methods that enable researchers to analyze and interpret their data, and ultimately build theory from it. Highly accessible in their approach, Corbin and Strauss provide a step-by-step guide to the research act--from the formation of the research question through several approaches to coding and analysis, to reporting on the research. Full of definitions and illustrative examples, this book concludes with chapters that present criteria for evaluating a study, as well as responses to common questions posed by students of qualitative research. Significantly revised, Basics of Qualitative Research remains a landmark volume in the study of qualitative methods.